Proteomic dynamics of breast cancer cell lines identifies potential therapeutic protein targets - Sun, Rui; Ge, Weigang; Zhu, Yi; Sayad, Azin; Luna, Augustin; Lyu, Mengge; Liang, Shuang; Tobalina, Luis; Rajapakse, Vinodh N.; Yu, Chenhuan; Zhang, Huanhuan; Fang, Jie; et al. (Molecular & cellular proteomics, 2023)
Treatment and relevant targets for breast cancer (BC) remain limited, especially for triple-negative BC (TNBC). We identified 6091 proteins of 76 human BC cell lines using data-independent acquisition (DIA). Integrating our proteomic findings with prior multi-omics datasets, we found that including proteomics data improved drug sensitivity predictions and provided insights into the mechanisms of action. We subsequently profiled the proteomic changes in nine cell lines (five TNBC and four non-TNBC) treated with EGFR/AKT/mTOR inhibitors. In TNBC, metabolism pathways were dysregulated after EGFR/mTOR inhibitor treatment, while RNA modification and cell cycle pathways were affected by AKT inhibitor. This systematic multi-omics and in-depth analysis of the proteome of BC cells can help prioritize potential therapeutic targets and provide insights into adaptive resistance in TNBC.